State ownership, board characteristics and corporate financial performance in publicy listed firms in Vietnam - Quang Minh Nguyen; Chien V. Nguyen (Cogent Social Sciences, 2024)
AbstractState ownership plays an important role in guiding corporate governance to achieve a number of government objectives. Therefore, using this capital can help businesses achieve high profits and growth. In addition, the characteristics of the board are also significant for increasing the profitability of the business. Using a sample data of 30 large companies with large market capitalization as well as great market influence listed on stock exchanges in Vietnam; and using the traditional regressions such as OLS, FEM and REM as well as the endogenous analysis, the research results indicated that state ownership has a positive contribution to financial performance. Moreover, larger board size is significantly consistent with higher financial performance. The study also affirmed that enterprises should choose equity instead of debt to ensure higher financial benefits for businesses.